LASSO Technique Application in Stock Market Modelling: An Empirical Evidence in Indonesia - Budi Setiawan (Faculty of Economics, Universitas Sriwijaya, 2018)
The stock market has captured the attention of many investor communities and scholars. It has become one of the most crucial aspects of a modern market economy. This study aims to determine the LASSO technique applications on the stock market in Indonesia. Furthermore, this research also compare linear regression techniques using the least squares method and using the LASSO approach to find out which model is the most appropriate and simple in making the estimation. The data is composed of daily closing stock price over the period from January 1,2000 to December 31, 2014. The results suggest that the best model in Indonesia Stock Market data of 2000-2014 is using LASSO techniques due to more simpler and the result of estimation relatively similar with least square regression model.